An Idyll as a Fragment of Russian Germans’ World Picture - Зейферт, Елена (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2022)
The appeal of Russian Germans to the genre situation and signs of idyll is largely due to the desire to find rest and harmony in a serene artistic reality, to create a world image of peace and tranquility. The idyll of Herbert Henke has a certain tendency to converge with a landscape meditative elegy, but, not allowing the mood of disappointment and sadness in its tonality, it retains an idyllic constant – a serene tone – and many of its dominants: limited topos, idyllic motives, themes, situations (“Shore”, solitude, fishing), landscape elements, an observer from the side, statics, and visualisation of images. An analysis of the entire Russian-German idyllic corpus (46 texts) outlines the contours of a meta-idyll in the poetry of Russian Germans, features of which, in addition to those noted by Herbert Henke, generate the image of a person in the centre of the artistic world and the high frequency of motives of the motherland and home. The reason for this may be the comprehension in the lyrics of the tragic fate of Russian Germans, a total penetration into the lyrical fabric of drama. When entering an interaction with the ethnic picture of the world of Russian Germans, the idyll activates features such as serene tonalities, a motivational field with the semantics of peace and tranquility, limited topos, and the absence of social problems. They begin to correlate with ethnic elements such as the “awareness of one’s surroundings by someone else”, “being inside another”, a “genetic fear of exile”, “striving for autonomy”, the “priority of statics over dynamics”. The negative semantics of ethnic elements (“alien”, “fear”, “exile”, “dependence”) partly neutralises the positive fullness of the idyllic image, weakening the constant, namely the tone of serenity.